Random Amplified Polymorphic DNA and Phenotyping Analysis of Salmonella enterica Serovar Enteritidis Isolates Collected from Humans and Poultry in Uruguay from 1995 to 2002 - Betancor, Laura (American Society for Microbiology, 2004)
Molecular and phenotyping techniques were applied to study Salmonella enterica serovar Enteritidis strains both from human cases of infection and of avian origin isolated in Uruguay from 1995 to 2002. A group of 62 isolates was subjected to random amplified polymorphic DNA (RAPD) assay and analysis of antibiotic resistance patterns. Twenty-one of these strains were further characterized by phage typing and analysis of their protein expression profiles. RAPD fingerprinting with five different primers discriminated 10 different genetic profiles. Of the 62 strains tested, 48 had a single major genetic profile, whereas the other nine profiles were evenly distributed among the other strains. The genetic diversity was greater among strains of animal origin than among isolates of human origin. Comparative examination of the results obtained by RAPD analysis and phenotypic analysis and by strain source provided evidence of the reliable discriminatory power of RAPD analysis in our study. Six avian isolates with antibiotic resistance were detected: two were nalidixic acid resistant and four had a particular β-lactam resistance pattern. The last four isolates all had the same unusual phage type (phage type 4b); however, RAPD analysis differentiated them into two groups. Two isolates with unique RAPD profiles were recovered from distinct human cases, suggesting that the technique differentiates unrelated strains. Overall, the results show the existence of a predominant genetic type that is present in poultry and that is transmitted to humans. There are also several other genotypes, but only a few of them could be recovered from human sources, suggesting the existence of different pathogenic traits among strains circulating in the country.